EVOLUSI PEDAGOGI GURU AGAMA KRISTEN SEBAGAI UPAYA PENINGKATAN MINAT BELAJAR SISWA DI ERA 4.0 - Manafe, Charisma Gianno Daviny; David Baluseda; Halawa, Yanuardin; Siringoringo, Maruhal (STT Ebenhaezer Tanjung Enim, 2022)
In responding to the current developments, every Christian religion teacher must evolve with the use of pedagogy to increase student interest in learning, with the achievement of soft skills that Christian religious teachers must possess in their teaching, namely, first the teacher must understand that the teacher is a calling in service so that it requires exemplary life, second, the need for creativity in teaching, thirdly creating a good relationship between teachers and students, the fourth teacher must be able to collaborate with the internet and digital that is developing at this time. The research method uses a qualitative approach or paradigm, which explains the importance of the evolution of Christian religious teachers and highlights several points regarding the basic reasons why pedagogy must develop. There are also interview methods from several Christian religious teachers in responding to the evolution of Christian religious teachers in the 4.0 era in order to get research results that are closer to the reality that is happening today. So the purpose of writing this scientific paper is the formation and creation of teachers who are able to compete with the current developments and create a lively learning atmosphere in order to increase student interest in learning.